SMART SAVING: MENGUBAH KEBIASAAN KECIL MENJADI KEBEBASAN FINANSIAL - Daffa Ahmad Athalla; Hilda Khoirunnisa; Nazwa Safitri (Jurnal Pengabdian Tangerang Selatan [JURANTAS], 2026)
Financial literacy is a fundamental competency that should be introduced from an early age to develop responsible financial behavior, particularly given the persistently low levels of financial literacy among Indonesian children relative to developed countries and the OECD average. Limited understanding among children regarding the importance of saving and managing pocket money may hinder the formation of positive financial habits in the future, a concern that is also reflected in international assessments of students' financial literacy. Therefore, this Community Service Program (PKM) implemented the "Smart Saving: Transforming Small Habits into Financial Freedom" program for children at Griya Yatim and Dhuafa, Kelapa Dua, Tangerang Regency. The program aimed to improve participants' understanding of financial literacy, the importance of saving from an early age, and their ability to distinguish between needs and wants in daily life. The implementation employed a polite and educational approach consisting of presentations, storytelling, interactive discussions, educational games, question-and-answer sessions, and practical saving activities using piggy banks. Program evaluation was conducted through direct observation of participants' involvement, their ability to answer questions, and their overall responses throughout the activities. The results indicated that participants actively engaged in the program, demonstrated a better understanding of basic financial management concepts, and became more aware of the importance of setting aside part of their pocket money for savings. The distribution of piggy banks also increased participants' motivation to develop sustainable saving habits. Overall, the Smart Saving program proved to be an effective educational medium for fostering financial literacy among children through enjoyable learning methods tailored to their characteristics.